Comparing Correlation-Based Feature Selection and Symmetrical Uncertainty for Student Dropout Prediction - Haryono Setiadi; Larasati, Indah Paksi; Esti Suryani; Wardani, Dewi Wisnu; Wardani, Hasan Dwi Cahyono; Ardhi Wijayanto (Ikatan Ahli Informatika Indonesia (IAII), 2024)
Predicting student dropout is essential for universities dealing with high attrition rates. This study compares two feature selection (FS) methods—correlation-based feature selection (CFS) and symmetrical uncertainty (SU)—in educational data mining for dropout prediction. We evaluate these methods using three classification algorithms: decision tree (DT), support vector machine (SVM), and naive Bayes (NB). Results show that SU outperforms CFS overall, with SVM achieving the highest accuracy (98.16%) when combined with SU Moreover, this study identifies total credits in the fourth semester, cumulative GPA, gender, and student domicile as key predictors of student dropout. This study shows how using feature selection methods can improve the accuracy of predicting student dropout, helping educational institutions retain students better.